Necessity and Obligation Modals in English Academic Discourse: A Corpus-Based Analysis - Ikmi Nur Oktavianti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Modals are linguistic units that seem to be ubiquitous in nearly all genres and text categories. However, there are some tendencies in which some modals are more likely to occur in a particular text category than the others. It is said that modals are less frequent in academic texts compared to fiction and news. This paper then aims at describing the modals, focusing to those expressing necessity/obligation, by using corpus-based analysis. This study uses a general reference corpus, Corpus of Contemporary American English, and compiled the data from the academic subcorpus. The results show that statistically the usage frequency of necessity and obligation modals is negligible; however, no matter how small it is, it still purports to mark something. Among the modals in the same category there are some tendencies, e.g. modal should is the most frequent of all, followed by must, have to, shall, be supposed to, and have got to. The collocate analysis focuses on should and must and found out that the most frequent verb type following these two modals belong to thinking verbs (e.g., consider, learn, understand). However the most frequent modal constructions are should have and must have enabling a slightly different interpretation. Besides, due to the nature of language in an academic setting, it is thus predictable that the use of the core modals (e.g., should, must) is more frequent than the quasi-modals (e.g., have to).